Compatibility of local government’s websites with the government of Nepal’s websites standards - Pokharel, Keshab Raj; Malla, Vijaya (Innovative Research Journal, 2022)
E-government generally refers to utilizing IT, ICTs, and other web-based communication technologies to improve and develop the efficiency and effectiveness of service delivery in the public sector. It is the utilization of IT, ICTs, and other web-based communication technologies to improve and develop the efficiency and effectiveness of service delivery in the public sector. E-government generally refers to the utilization of IT, ICTs, and other web-based communication technologies to improve and develop the efficiency and effectiveness of service delivery in the public sector. Most of the government organizations in Nepal have their own websites and their website has been used as a tool for making information easy to find, for ease of obtaining services, designed with mobile in mind, notify citizens about their recent activities and notices, gather feedback, inter- and intra-organizational information exchange and many more. Since Local Government have started to use their websites as an information center, effective website design and functionality is very important for providing services to the citizens. Developing countries like Nepal are lagging behind in e-government adoption compared to developed countries. During the last 10-15 years, governments from all over the world have tried to take advantage of IT and the Internet to improve governmental administration and communication with their people. Also, Nepal has tried its best to achieve this. As IT offers the opportunity for the government to better deliver information and services and to interact with citizens, businesses, and other government stakeholders in an effective manner. The discrepancy in e-government implementation between regions in Nepal is huge due to a number of reasons, including management, infrastructure, and human factors that vary across this heterogeneous country.